(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
Cotton terry fabric is a cornerstone of the global textile market, valued for its exceptional water absorbency, which is intrinsically linked to the quality and structure of its pile loops. The manufacturing process is highly sensitive to loom configurations, particularly pile yarn tension and pile height, which directly influence key performance attributes such as absorbency, softness, and mechanical strength. Inconsistent settings can lead to significant production waste and subpar product quality. This study sought to systematically determine the optimal combination of pile yarn tension and pile height to maximize the absorbency rate and loop uniformity of 100% cotton terry fabric while preserving acceptable levels of tensile strength. A full factorial experimental design was implemented, producing nine distinct terry fabric samples on a modern electronic dobby loom. The independent variables were pile yarn tension (15 cN, 20 cN, 25 cN) and pile height (2mm, 3mm, 4mm). The fabricated samples were rigorously tested for water absorbency rate (AATCC 79), loop uniformity via digital image analysis, and warp-wise tensile strength (ASTM D5034). The results demonstrated a significant positive correlation between pile height and absorbency, with the 4mm high-pile samples absorbing water 25-35% faster than the 2mm samples. Loop uniformity was optimal at a medium tension of 20 cN, which produced well-defined and consistent loops, whereas low and high tensions resulted in irregular and stiff loops, respectively. A key trade-off was identified, as increasing the pile height led to an 8-12% reduction in warp-wise tensile strength. The findings confirm that a "medium tension, high pile" configuration (20 cN, 4mm) yields the superior performance for applications prioritizing absorbency and softness, such as bathrobes and luxury towels, despite a marginal sacrifice in strength. This research provides a quantitative framework for manufacturers to optimize loom settings, thereby enhancing product quality, reducing defects, and aligning production with specific market demands.